2014
DOI: 10.1364/ol.39.002971
|View full text |Cite
|
Sign up to set email alerts
|

Third-order chromatic dispersion stabilizes Kerr frequency combs

Abstract: Using numerical simulations of an extended Lugiato-Lefever equation we analyze the stability and nonlinear dynamics of Kerr frequency combs generated in microresonators and fiber resonators, taking into account third-order dispersion effects. We show that cavity solitons underlying Kerr frequency combs, normally sensitive to oscillatory and chaotic instabilities, are stabilized in a wide range of parameter space by third-order dispersion. Moreover, we demonstrate how the snaking structure organizing compound s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 29 publications
10
75
1
Order By: Relevance
“…In the anomalous dispersion regime, such temporal oscillations, also called "breathers", were experimentally first observed in fiber resonators [12] and have recently also been measured in microresonators [48][49][50]. In the anomalous regime, it was furthermore shown that TOD, which leads to drift instabilities, could suppress such oscillatory and chaotic temporal dynamics of bright solitons [26,27].…”
Section: Suppression Of Temporal Soliton Instabilitiesmentioning
confidence: 91%
See 3 more Smart Citations
“…In the anomalous dispersion regime, such temporal oscillations, also called "breathers", were experimentally first observed in fiber resonators [12] and have recently also been measured in microresonators [48][49][50]. In the anomalous regime, it was furthermore shown that TOD, which leads to drift instabilities, could suppress such oscillatory and chaotic temporal dynamics of bright solitons [26,27].…”
Section: Suppression Of Temporal Soliton Instabilitiesmentioning
confidence: 91%
“…6 is to be interpreted as a drift in the fast time scale of the resonator round trip (where τ is scaled by √ 2α/ √ |β 2 |l) per time unit t (where t depends on the photon lifetime as t × α/t r with t r the round-trip time) [12,35]. This drift velocity thus strongly depends on α and l, which can change significantly from device to device (see, e.g., [27]). As solitons of different widths travel at different speeds, they eventually collide in a periodic domain and are forced to interact with one another.…”
Section: Soliton Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently an intense research activity aiming to maximise the spectral extent of the comb and its coherence, and to understand the experimentally obtained spectra from first principles. Due to the extremely complex dynamical behaviour and stability properties of the propagating CSs and patterns in the resonators, an intense theoretical activity on the mathematical properties of the traditionally used averaged propagation equation, called the temporal Lugiato-Lefever equation (LLE), has developed over the past years, with a frequent display of new and surprising results [3][4][5][6][7].…”
mentioning
confidence: 99%